Tożsamość i pamięć zbiorowa w badaniach politologicznych - Lipiński, Artur (Przegląd Politologiczny, 2018)
The social sciences have experienced an unprecedented interest in the issue of collective memory dating back at least to the 1990s. There has been a veritable avalanche of studies into this topic, editorial series and periodicals have appeared devoted exclusively to it. Simulta- neously, an analysis of the literature on this topic shows that collective memory is not a partic- ularly frequent subject of political science research. It is therefore routine in many works of political scientists to acknowledge the limited number of studies on memory. All that does not mean that the trend has not begun slowly to change. The number of texts on the political as- pects of memory is systematically growing, there are editorial series and monographic issues of scientific periodicals concerning the issue of memory or the political instrumentalization of history. Political scientists are also co-authors of collective works and periodicals of an inter- disciplinary character. The objective of this paper is to analyze a single, but highly influential, issue related to political science research into memory, namely the topic of identity perceived from the perspective of collective memory. The purpose is not so much the exhaustive presen- tation of all the surveys into memory and collective identity in the field of political science but rather establishing the set of main concepts, themes and issues explored by political science literature written in English.